Influence of Board Directors, Independent Commissioners, Audit Committee on CSR - Afriatun Khasanah; Nur Isna Inayati; Iwan Fakhruddin; Bima Cinintya Pratama (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research aims to determine how the size of the board of directors, educational background of directors, representation of female directors, proportion of independent commissioners, and audit committees affect CSR. The population in this research is General Banking companies listed on the Indonesia Stock Exchange. The sample used is a general banking company registered on the IDX that publishes annual and sustainability reports. Forty-two conventional general banking company sectors were sampled in the research for the 2018-2022 period. The method used is the panel regression method. This research hypothesis test shows that there is an influence on the educational background of directors. This is because, with more diversity in the educational background of directors, there will be more diversity in supervision, insight, perception, and different skills and expertise on each board of directors, which will complement each other. The variable proportion of independent commissioners also positively affects CSR disclosure. This supports the theory of stakeholders because the decisions taken by the company will be more objective and able to protect all stakeholders. Meanwhile, the variables number of board of directors, representation of women directors, and number of audit committees do not influence CSR.                             Keywords: Size of Board of Directors, Educational Background of Directors, Representation of Female Directors, Proportion of Independent Commissioners, Size Audit Committee, and CSR